Post-Soviet Capitalism in Russia and Digital Revolution. (July 2022) - Dzarasov, Ruslan; Gritsenko, Viktoria
The article examines characteristics of digitalization in the Russian economy in its connection with the semi-peripheral position of Russia. The reasons for the lack of efficiency of Russian digitalization and its uneven development in various economy sectors are explained. According to the authors, the root causes of this state of affairs can be seen even in the patterns of the degeneration and disintegration of the Soviet Union, when the features of rent-seeking behavior of the ruling elite were first identified. The article presents the results of a study into the needs for information resources in the sectors of the Russian economy (in comparison with the group of reference countries), which reflect the decline in those in industry and, on the contrary, the concentration in the research and development sector. The authors believe that these data confirm the conclusion about the selective and generally insufficient character of digitalization.